What have we learned from observational studies and clinical trials of mild to moderate COPD? - Miriam Barrecheguren; Cruz González; Marc Miravitlles (Respiratory Research, 2018)
Abstract Chronic obstructive pulmonary disease (COPD) is a major cause of morbidity and mortality worldwide. It is well established that patients with mild to moderate disease represent the majority of patients with COPD, and patients with mild COPD already have measurable physiological impairment with increased morbidity and a higher risk of mortality compared with healthy non-smoking individuals. However, this subpopulation is both underdiagnosed and undertreated. In addition, most clinical trials include cohorts of patients with worse lung function and quality of life, which are very different from the milder patients usually seen in primary care. Clinical trials have shown that mild-moderate COPD patients present an improvement in lung function after treatment with long-acting bronchodilators (LABD). Inhaled therapy has also shown benefits in terms of symptoms, health-related quality of life (HRQL) and exacerbation prevention in this population. Early intervention might have also a positive effect to prevent functional impairment. Nevertheless, there is scarce evidence from randomised clinical trials and real-life studies about the importance of pharmacological treatment in early stages of COPD to improve long-term outcomes. New concepts such as clinically important deterioration may help to investigate the impact of interventions on the natural history of the disease.